A macro model for shallow foundations on granular soils describing non-linear foundation behavior. (May 2020) - Tistel, J.; Grimstad, G.; Eiksund, G.R.
Highlights: Macro model describing non-linear behavior for a shallow foundation on granular soil. The model presented within this paper is non-associated. The paper demonstrates the model calibration process and model precision. Validation by laboratory testing is presented in the paper. Use of the model is exemplified by a suspension bridge anchor block foundation. The model demonstrates good agreement with FEA and laboratory test results. The model can be applied for a variety of surface foundations on granular materials. The model demonstrates a new application of the macro model concept. Abstract: This paper describes a macro model for a shallow foundation. The macro model represents the non-linear soil structure interaction (SSI) exemplified by a suspension bridge anchor-block. The model can be adjusted and used for other structures. The formulation uses an elasto-plastic framework to calculate the foundation response. A yield surface in the V – M - H (Vertical, Moment and Horizontal loading) load-space defines the yield and failure envelopes. A non-associated potential surface and a simple bi-linear hardening law describe the magnitude as well as the direction of the plastic displacements. Calibration of model parameters are performed through 2D and 3D finite element calculations. The model is suited for integration in a program for structural design. Compared to a full finite element model, the macro model simplifies the soil structure interaction analyses significantly. The yield and potential surfaces include the option to modify the shape in the H − V plane versus the M − V plane. Allowing for this flexibility in the formulation improves modeling of foundation uplift behavior. The paper demonstrates calibration of macro model parameters through a calculation example. Validation of the model by prototype testing in a sand bin is also performed and presented.